URGENSI HISTORICAL THINKING SKILLS BAGI PESERTA DIDIK DALAM PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM - Achmadin, Balya Ziaulhaq (Muta'allim: Jurnal Pendidikan Agama Islam, 2022)
Historical thinking skill is the ability to think historically related to how to identify in critical and deep thinking about history. This historical ability is important for students to have, because critical thinking is a representation of the universal, multicultural and democratic character of citizens. With this model of thinking development model, it is hoped that students can be more critical and thorough in determining life in the future. The pattern of developing historical thinking is adjusted to the age or level of education of the students. Learners are human beings who are in a state of resistance to development and growth, students are considered immature so they need guidance from parents and educators in the development process which is certainly at every level of education has its own educational focus according to the abilities of students whose ending when entering the age of late adolescence will there are cognitive, affective and psychomotor changes of learners which are obtained through the process of education and teaching at every level of education. Abstrak Historical thingking skill merupakan kemampuan berpikir historis yang berkaitan dengan cara mengidentifikasi dalam berpikir kritis dan mendalam mengenai sejarah. Kemampuan kesejarahan ini penting dimiliki oleh peserta didik, karena berpikir kritis adalah representasi karakter warga negara yang universal, multikultural dan demokratis. Dengan model pengembangan berpikir model ini diharapkan agar peserta didik dapat lebih kritis dan teliti dalam menentukan kehidupan di masa mendatang. Pola pengembangan berpikir historis disesuaikan dengan usia atau jenjang pendidikan peserta didik. Peserta didik merupakan seorang insan yang berada dalam tahan perkembangan dan pertumbuhan, peserta didik dianggap belum dewasa sehingga perlu bimbingan orang tua maupun pendidik dalam proses perkembangannya yang pastinya dalam setiap jenjang pendidikan memimiliki fokus pendidikan tersendiri sesuai kemampuan peserta didik yang endingnya ketika memasuki usia remaja akhir akan terjadi perubahan kognitif, afektif dan psikomotorik peserta didik yang di peroleh melalui proses pendidikan dan pengajaran di setiap tingkatan pendidikannya.